Analisis manajemen resiko dalam pengiriman Cash on Delivery (COD) pada shopee e-commerce - Nasikhah, Mazroatun; Segaf, Segaf (Maliki Interdisciplinary Journal, 2024)
This research examines risk management in Cash on Delivery (COD) deliveries on the Shopee e-commerce platform. The proliferation of electronic commerce, including in Indonesia, has changed consumption patterns with efficient and fast services. COD is an offline payment option commonly used in e-commerce, including Shopee. Despite the increasing popularity of COD, new challenges have emerged, most notably unilateral order cancellations by buyers without the seller’s consent. Previous research shows that several factors causing COD order cancellations include changes in buyer decisions, limited buyer funds, inadvertent order placement, buyer unavailability for communication, and misuse or damage to orders. These risks impact sellers, such as workforce depletion, financial harm, lost time, and reduced store performance. This research aims to provide a comprehensive risk management analysis regarding unilateral order cancellations that occur in COD deliveries on Shopee E-commerce. It is hoped that the results of this research can become a source of insight and literature as well as an evaluative source for e-commerce platforms that use cash payments on delivery in the future.